Spesies Semut (Hymenoptera: Formicidae) yang di Koleksi dengan Metode All Protocol pada Perkebunan Sawit (ElaeisguineensisJacq.) dan Hutan di Kanagarian Kunangan Parik Rantang Kabupaten Sijunjung - Susanto, Oki Kobayasi; Herwina, Henny; Zeswita, Armein Lusi (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Study about ants spesies in palm oil plantation (Elaeis guneensis jacq.) and forest in Kanagarian Kunangan Parik Rantang Sijunjung District West Sumatera were conducted by using ALL protocol method on March of 2013. A total of 20 species that belonging to 15 genera, 9 tribe and three subfamilies of ants was collected. Formicinae and Myrmicinae were found as the highest in number of species (6 species each) in palm oil plantation, meanwhile Ponerinae was the highest in forest (7 species).Â